2014
DOI: 10.3390/v6093563
|View full text |Cite
|
Sign up to set email alerts
|

The Adenovirus Genome Contributes to the Structural Stability of the Virion

Abstract: Adenovirus (Ad) vectors are currently the most commonly used platform for therapeutic gene delivery in human gene therapy clinical trials. Although these vectors are effective, many researchers seek to further improve the safety and efficacy of Ad-based vectors through detailed characterization of basic Ad biology relevant to its function as a vector system. Most Ad vectors are deleted of key, or all, viral protein coding sequences, which functions to not only prevent virus replication but also increase the cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
39
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(43 citation statements)
references
References 144 publications
(199 reference statements)
4
39
0
Order By: Relevance
“…It is possible that inactivation of E3 13.7K protein expression disrupts the stability of the hexon shell, leading to production of fragile capsids, which may be broken due to harsh treatment during CsCl/TEM procedures. Alternatively, it is possible that production of virions with fragile capsids could be due to the inefficient packaging of virion DNA (48). Several lines of evidence suggest that the capsid instability could be due to the loss of interaction of 13.7K with other adenovirus cement proteins.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that inactivation of E3 13.7K protein expression disrupts the stability of the hexon shell, leading to production of fragile capsids, which may be broken due to harsh treatment during CsCl/TEM procedures. Alternatively, it is possible that production of virions with fragile capsids could be due to the inefficient packaging of virion DNA (48). Several lines of evidence suggest that the capsid instability could be due to the loss of interaction of 13.7K with other adenovirus cement proteins.…”
Section: Discussionmentioning
confidence: 99%
“…This result indicates that the modularised genome of decompressed φX174 is having a negative effect on the thermal stability of the virion. This is not totally unexpected, as studies addressing heat stability of viral capsids with genomic variation have revealed different thermal stability between counterparts (Emerson, Arankalle et al, 2005, Ojosnegros, García-Arriaza et al, 2011, Saha, Wong et al, 2014. The physical properties of constituents within capsid shells (for example, salt ions and nucleotides) have been shown to directly influence a capsid's internal osmotic pressure, and consequently, mechanical stability (Evilevitch, Fang et al, 2008, Evilevitch, Lavelle et al, 2003, Ivanovska, Wuite et al, 2007, Roos, Bruinsma et al, 2010.…”
Section: Decompressed φX174 Virion Has Poor Heat Stability and Attachmentioning
confidence: 95%
“…The first adenoviral genome to be sequenced was from subtype 2 (Ad2), composed of 35,937 base pairs (bp) [29]. Since then, the majority of subtypes have been sequenced and found to have similar genome organisation and functional gene products as Ad2, including Ad5.…”
Section: Structure Of Adenovirusesmentioning
confidence: 99%